2005
DOI: 10.1111/j.1472-8206.2005.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptors: promising targets for the development of novel therapeutics and diagnostics for asthma

Abstract: Interest in the role of adenosine in asthma has escalated considerably since the early observation of its powerful bronchoconstrictor effects in asthmatic but not normal airways. A growing body of evidence has emerged in support of a proinflammatory and immunomodulatory role for the purine nucleoside adenosine in the pathogenic mechanisms of chronic inflammatory disorders of the airways such as asthma. The fact that adenosine enhances mast cell allergen-dependent activation, that elevated levels of adenosine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 108 publications
0
23
0
Order By: Relevance
“…Adenosine is an endogenous nucleoside present at low levels under normal conditions; however, its concentrations increase in the setting of stress and inflammation [177]. Adenosine has proinflammatory and immunomodulatory effects and may be involved in the pathogenesis of asthma [178-180].…”
Section: Pathophysiologic Links Between Asthma and Depressionmentioning
confidence: 99%
“…Adenosine is an endogenous nucleoside present at low levels under normal conditions; however, its concentrations increase in the setting of stress and inflammation [177]. Adenosine has proinflammatory and immunomodulatory effects and may be involved in the pathogenesis of asthma [178-180].…”
Section: Pathophysiologic Links Between Asthma and Depressionmentioning
confidence: 99%
“…In fact, level of adenosine in serum, bronchoalveolar lavage (BAL) or exhaled breath condensate (EBC) is significantly greater in asthmatics than in healthy people [6][7][8][9]. Furthermore adenosine concentration increases in nasal lavage fluid and also in EBC is increased in patients with allergic rhinitis [10]. The question however remains what are the benefits (or harms) of high adenosine level in the airways.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of adenosine in asthma has been the subject of considerable attention over the years, after it was shown that it produced powerful bronchoconstriction in asthma, although it had little effect in healthy lungs; xanthines, antagonists of adenosine receptors, were widely used for treatment of asthma (for reviews, see Persson, 1982;Kawasaki et al, 1983;Holgate et al, 1987Holgate et al, , 1990Feoktistov and Biaggioni, 1996;Fozard and Hannon, 2000;Meade et al, 2001;Fozard and McCarthy, 2002;Holgate, 2002Holgate, , 2005Polosa et al, 2002;Fozard, 2003;Lee et al, 2003;Livingston et al, 2004;Caruso et al, 2006Caruso et al, , 2009Russo et al, 2006;Brown et al, 2008b;Wilson, 2008). It was suggested that the hyper-responsive effects of adenosine in isolated bronchi was due to indirect actions by liberation of histamine and leukotrienes (Björck et al, 1992).…”
Section: A Asthmamentioning
confidence: 99%